Heels in line - Pryce, J. E. (London : Arthur Barker, 1958)
Experiences of author after being picked up by the Germans after the cruiser "Gloucester" had been sunk in the Battle of Crete.
Keywords: Pryce, J. E; World War, 1939-1945 -- Prisoners and prisons, German; World War, 1939-1945 -- Personal narratives, British; Prisoners of war -- Germany -- Biography; Prisoners of war -- Great Britain -- Biography